Lymphotropic polyomavirus and Merkel cell polyomavirus in patients infected with HIV or hepatitis B or C virus - Bahman Abedi Kiasari; Amir Hossein Alipour; Negar Hemmati; Mohammad Gholamnezhad; Fatemeh Hoda Fallah (New Microbes and New Infections)
Background: LPV and MCV emerge as recent additions to the Polyomaviridae family, capable of inducing important infections. Studies have suggested the presence of LPV in human populations, with potential involvement in central nervous system (CNS) diseases. Additionally, MCV, closely related to LPV, has been implicated in Merkel cell carcinoma (MCC). This study aimed to explore the prevalence of LPV and MCV in individuals with compromised immunity due to chronic viral infections. Methods: 340 specimens, including HIV PCR-positive, HBV PCR-positive, HCV PCR-positive, and HIV/HBV/HCV negative sera, underwent screening via PCR technique to identify LPV and MCV genomes. Subsequently, sequencing was employed to validate the viral identity. Results: Out of all specimens, MCV DNA was detected in 8.52 % of participants, with a significantly higher prevalence in HIV-positive individuals (26.4 %). LPV was detected in only one HIV-positive patient. No co-detection of MCV and LPV was observed. Phylogenetic analysis confirmed the genetic similarity of the detected MCV strains to known references, while the LPV sequence showed 99 % identity to the published sequences of LPV-K38. Conclusion: This research provides insights into the prevalence of LPV and MCV in individuals with chronic viral infections. The study highlights the potential association between MCV and immunocompromised states, emphasizing the need for comprehensive investigations to understand the epidemiology, transmission routes, and clinical implications of these polyomaviruses in human populations.